Developing Dirasah Islamiyah Materials Based on Character Values for Afkaaruna Islamic School - Zahrah, Siti Fatimatuz; Kholis, Adhan (STAI Syaichona Moh. Cholil Bangkalan, 2023)
Integrating character values on materials is essential. This research aimed to develop Dirasah Islamiyah teaching materials based on character values for the fifth-grade students of Afkaaruna Islamic School Yogyakarta. The learning materials, especially Dirasah Islamiyah presented, still needed to be fully integrated with character values. This research was a research and development (R&D) study referred to the Thomlinson model, which included need analysis, stating goals and objectives, designing a syllabus design, developing methodology/material, and conducting testing and evaluation. Needs analysis questionnaires were employed as the instrument for collecting data. The data obtained from the need analysis was analyzed quantitatively. Afterwards, the course grid was developed. The material developed was I Love Good Muamalah and developed into three sub-themes. Although each sub-theme had a different number of tasks, it followed the unit design of which the components were: (1) introduction; (2) main lesson; and (3) reinforcement. The results of the expert judgment showed that the developed materials were appropriate and deserved to be used. The mean values of all aspects were 71, categorized as